Making haste from Babylon : the Mayflower Pilgrims and their world : a new history - Bunker, Nick. (New York : Vintage Books, 2011)
Details the voyage of Pilgrims on the "Mayflower" and describes the Plymouth Colony, focusing on events during the 1620s and discussing religion, politics, money, science, and other related topics.
Includes bibliographical references (p. [429]-467) and index.
Booklist
Library Journal Starred
Pub Weekly
Booklist, March 2010
Choice, October 2010
Keywords: Mayflower (Ship); Pilgrims (New Plymouth Colony); Massachusetts -- History -- New Plymouth, 1620-1691.